2010
DOI: 10.1002/app.32282
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline/carbon black composite as Pt electrocatalyst supports for methanol oxidation: Synthesis and characterization

Abstract: Core/shell composites of polyaniline (PANI) and Vulcan XC-72 Carbon (VC), in which the carbon represents the core and PANI forms the shell, were synthesized by in situ chemical oxidation polymerization. Platinum (Pt) particles were then deposited on the PANI/ VC composites by chemical reduction method. The highest conductivity is obtained when a mass ratio of PANI/VC equals to 0.28, as proved by Fourier transform infrared spectra. And it is also proved that there are some reactions happened between PANI and VC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The IR spectra of ES samples treated with higher cation radical and emeraldine to pernigraniline transitions. The highest current densities corresponding to the anodic peaks are observed in H 2 SO 4 than in HCl, which is also supported by different authors [26,32,33]. Thus, the CVs clearly reveal the formation of electroactive PANI polymer films in both supporting electrolytes.…”
Section: Ir Spectroscopy Of Panisupporting
confidence: 81%
See 1 more Smart Citation
“…The IR spectra of ES samples treated with higher cation radical and emeraldine to pernigraniline transitions. The highest current densities corresponding to the anodic peaks are observed in H 2 SO 4 than in HCl, which is also supported by different authors [26,32,33]. Thus, the CVs clearly reveal the formation of electroactive PANI polymer films in both supporting electrolytes.…”
Section: Ir Spectroscopy Of Panisupporting
confidence: 81%
“…The conductivity and electrical properties were done by using the digital multimeter with lead metal roads inserted in the solutions and also using pH-ISE [32]. Then, the current-voltage measurements were done using the two-point probe method and resistivity measurements were carried out by using equation given below.…”
Section: Conductivity Measurementsmentioning
confidence: 99%
“…It has been reported that conducting polymers (CPs) could behave as a suitable host material for dispersing metallic particles [15][16][17][18]. Most literatures showed that the enhanced activity of Pt-based catalysts on CPs for the oxidation of organic molecules is associated with their high surface area and the synergistic effect between CPs and Pt catalysts [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Conducting polymers have been extensively used since last four decades as novel materials for potential applications in various electrochemical devices including actuators (Shoa et al 2010), chemical and biosensors (Koh et al 2010), capacitors (Lee et al 2010) and electrocatalyst (Qu et al 2010). The most commonly applied polymers for sensing applications have been based on polypyrrole (pPy), polyaniline (PANI), polythiophene (PTP) and their derivatives (Pirsa and Alizade 2010).…”
Section: Introductionmentioning
confidence: 99%